2020
DOI: 10.3389/fimmu.2020.557960
|View full text |Cite
|
Sign up to set email alerts
|

Littermate-Controlled Experiments Reveal Eosinophils Are Not Essential for Maintaining Steady-State IgA and Demonstrate the Influence of Rearing Conditions on Antibody Phenotypes in Eosinophil-Deficient Mice

Abstract: Conflicting data has emerged regarding a role for eosinophils in IgA production, with some reports that eosinophils support both secretory and circulating IgA levels during homeostasis. Previous studies have compared antibody levels between wildtype and eosinophil-deficient mice, but these mice were obtained from different commercial vendors and/or were not littermates. Thus, the possibility remains that extrinsic environmental factors, rather than an intrinsic lack of eosinophils, are responsible for the repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Our findings corroborate the data by FitzPatrick et al (2020), who described high levels of total SIgA under natural conditions and without infection in the absence of eosinophils [41]. However, we also found that eosinophils are essential for the maintenance of high levels of this immunoglobulin after infection with A. suum, corroborating the findings of previous studies [32,[44][45][46].…”
Section: Plos Pathogenssupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings corroborate the data by FitzPatrick et al (2020), who described high levels of total SIgA under natural conditions and without infection in the absence of eosinophils [41]. However, we also found that eosinophils are essential for the maintenance of high levels of this immunoglobulin after infection with A. suum, corroborating the findings of previous studies [32,[44][45][46].…”
Section: Plos Pathogenssupporting
confidence: 93%
“…Moreover, a local eosinophilic response may also induce an increased number of eosinophils in remote sites [ 76 ]. Although some variations in basal SIgA levels have been observed in non-infected mice before, the literature suggests that variations in the native microbiota are natural [ 41 ]. It has also been reported that WT BALB/c and WT C57BL/6 mice strains differ in polyreactive IgA abundance and specificity, as well as in microbiota diversity [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such and like in other known effector niches, secreted factors and cellular interactions synergistically contribute to IgA + PC survival in the LP. Moreover, eosinophil‐deficient mice have been shown to harbor an altered microbiota which may also explain why these mice have less IgA + PC 51,52 …”
Section: Effector Sites For Iga+ Plasma Cells During Homeostasismentioning
confidence: 99%
“…It has been postulated that eosinophilic granulocytes may be essential for plasma cell persistence, based on the analysis of mice deficient for eosinophils [71,72]. More recently, however, alternative explanations have been provided for this observation [73][74][75][76], and a subpopulation of bone marrow stromal cells expressing BAFF has been identified [55], suggesting that BAFF and/or APRIL can be provided by several cell types, including eosinophilic granulocytes, but obviously in a redundant fashion [56].…”
Section: Maintaining Immune Memory Cells: (Homeostatic) Proliferation Versus Stromal Cell Contact-induced Quiescencementioning
confidence: 99%